Analisis Kemampuan Literasi Matematis Ditinjau dari Mindset pada Materi Kesebangunan dan Kekongruenan - Sika, Monika; Firdaus, Muhamad; Susiaty, Utin Desy (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze mathematical literacy skills reviewed from the mindset on the material of versatility and congruence. The study uses a qualitative descriptive method with a case study research form. The population in this study were all class vii d of Smp Negeri 5 Sungai Kakap. By using the percussive sampling technique, a population of 31 students was obtained, with 6 samples being used as the main subjects based on the mindset category. The research aids include a mindset questionnaire, a mathematical literacy ability test and a semi-structured interview. The data is analyzed using quantitative descriptive methods. The results of the study showed that students who have a growth mindset with high category mathematical literacy skills are able to meet all indicators of mathematical literacy skills for students who have a fixed mindset in the medium category in mathematical literacy skills and only a few meet the indicators of mathematical literacy skills, especially in compiling situations mathematically.